2012
DOI: 10.1017/is012003003jkt185
|View full text |Cite
|
Sign up to set email alerts
|

KK-Theory and Spectral Flow in von Neumann Algebras

Abstract: We present a definition of spectral flow for any norm closed ideal J in any von Neumann algebra N . Given a path of selfadjoint operators in N which are invertible in N=J , the spectral flow produces a class in K 0 .J /.Given a semifinite spectral triple .A;H;D/ relative to .N; / with A separable, we construct a class OED 2 KK 1 .A;K.N //. For a unitary u 2 A, the von Neumann spectral flow between D and u Du is equal to the Kasparov product OEu Ő A OED, and is simply related to the numerical spectral flow, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 21 publications
0
45
0
Order By: Relevance
“…Our view is that the natural setting for the theory of spectral triples is not the bounded operators on a Hilbert space with its ideal of compact operators, but the corresponding situation in a general semifinite von Neumann algebra. This view is supported by [24], and we will amplify on this viewpoint later using results from [37].…”
Section: 2mentioning
confidence: 68%
See 2 more Smart Citations
“…Our view is that the natural setting for the theory of spectral triples is not the bounded operators on a Hilbert space with its ideal of compact operators, but the corresponding situation in a general semifinite von Neumann algebra. This view is supported by [24], and we will amplify on this viewpoint later using results from [37].…”
Section: 2mentioning
confidence: 68%
“…We remark that semifinite Kasparov modules and semifinite spectral triples provide information that is different from that of the standard theory [23]. We provide later in this article a summary of [37] where it is shown that a semifinite spectral triple for A represents an element of KK * (A, B), where B is the separable norm closed subalgebra of the compact operators in N generated by the resolvent of D and the commutators [F D , a] for a ∈ A where…”
Section: 2mentioning
confidence: 95%
See 1 more Smart Citation
“…In [23], Connes and Cuntz show that cyclic n-cocycles for an appropriate algebra A are in one-to-one correspondence with traces on a certain ideal J n in the free product A * A. Assuming some positivity for this trace yields the same kind of 'semi-finite Kasparov modules' as are described in [37]. In other words, to realise all the cyclic cocycles for an algebra will, in general, necessitate considering semifinite Fredholm modules and semi-finite spectral triples.…”
Section: Introductionmentioning
confidence: 92%
“…This is explained by a result of Kaad-NestRennie [37]. They show that a semifinite spectral triple for A represents an element of KK 1 (A, J), where J is the σ-unital norm closed ideal of compact operators in N generated by the resolvent of D and the commutators […”
Section: 2mentioning
confidence: 99%